Exome sequencing and functional analyses suggest that SIX6 is a gene involved in an altered proliferation–differentiation balance early in life and optic nerve degeneration at old age - Adriana I. Iglesias; Henriët Springelkamp; Herma van der Linde; Lies‐Anne Severijnen; Najaf Amin; Ben A. Oostra; Christel Kockx; Mirjam C. G. N. van den Hout; Wilfred F. J. van IJcken; Albert Hofman; André G. Uitterlinden; Robert M. Verdijk; et al. (2013)
Primary open-angle glaucoma (POAG) is a hereditary neurodegenerative disease, characterized by optic nerve changes including increased excavation, notching and optic disc hemorrhages. The excavation can be described by the vertical cup–disc ratio (VCDR). Previously, genome-wide significant evidence for the association of rs10483727 in SIX1–SIX6 locus with VCDR and subsequent POAG was found. Using 1000 genomes-based imputation of four independent population-based cohorts in the Netherlands, we identified a missense variant rs33912345 (His141Asn) in SIX6 associated with VCDR (Pmeta = 7.74 × 10−7, n = 11 473) and POAG (Pmeta = 6.09 × 10−3, n = 292). Exome sequencing analysis revealed another missense variant rs146737847 (Glu129Lys) also in SIX6 associated with VCDR (P = 5.09 × 10−3, n = 1208). These two findings point to SIX6 as the responsible gene for the previously reported association signal. Functional characterization of SIX6 in zebrafish revealed that knockdown of six6b led to a small eye phenotype. Histological analysis showed retinal lamination, implying an apparent normal development of the eye, but an underdeveloped lens, and reduced optic nerve diameter. Expression analysis of morphants at 3 dpf showed a 5.5-fold up-regulation of cdkn2b, a cyclin-dependent kinase inhibitor, involved in cell cycle regulation and previously associated with VCDR and POAG in genome-wide association studies (GWASs). Since both six6b and cdkn2b play a key role in cell proliferation, we assessed the proliferative activity in the eye of morphants and found an alteration in the proliferative pattern of retinal cells. Our findings in humans and zebrafish suggest a functional involvement of six6b in early eye development, and open new insights into the genetic architecture of POAG.